2013
DOI: 10.1590/s0103-90162013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Texture and organic carbon contents do not impact amount of carbon protected in Malagasy soils

Abstract: Soil organic carbon (SOC) is usually said to be well correlated with soil texture and soil aggregation. These relations generally suggest a physical and physicochemical protection of SOC within soil aggregates and on soil fi ne particles, respectively. Because there are few experimental evidences of these relations on tropical soils, we tested the relations of soil variables (SOC and soil aggregate contents, and soil texture) with the amount of SOC physically protected in aggregates on a set of 15 Malagasy soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…In this sense, it is worth mentioning excess moisture and very low temperatures (BALDOCK; NELSON, 2000), as well as the physical protection within soil microaggregates (CAMBARDELLA; ELLIOTT, 1993;FELLER, 2000;SIX et al, 2000) and chemical protection by bonds between organic and clay mineral compounds (PARFITT et al, 1997). However, in this study, the soil clay content was not the preponderant factor for OC accumulation, as reported elsewhere by Razafimbelo et al (2013). Therefore, the pine trees were decisive for soil TOC accumulation, as also shown by the negative correlation between the TOC and clay contents, and because the TOC levels and their POC and MAC fractions were highest precisely in the soil with the lowest proportion of this particle-size fraction.…”
Section: Total Particulate and Mineral-associated Organic Carbon Consupporting
confidence: 68%
“…In this sense, it is worth mentioning excess moisture and very low temperatures (BALDOCK; NELSON, 2000), as well as the physical protection within soil microaggregates (CAMBARDELLA; ELLIOTT, 1993;FELLER, 2000;SIX et al, 2000) and chemical protection by bonds between organic and clay mineral compounds (PARFITT et al, 1997). However, in this study, the soil clay content was not the preponderant factor for OC accumulation, as reported elsewhere by Razafimbelo et al (2013). Therefore, the pine trees were decisive for soil TOC accumulation, as also shown by the negative correlation between the TOC and clay contents, and because the TOC levels and their POC and MAC fractions were highest precisely in the soil with the lowest proportion of this particle-size fraction.…”
Section: Total Particulate and Mineral-associated Organic Carbon Consupporting
confidence: 68%
“…This accumulation and binding process is driven predominantly by the organic carbon content of the fractions (Tan et al, 2007;Guimara et al, 2013;Razafimbelo et al, 2013). The degrading microbes of PAHs were also distributed un-evenly through out the soil particles with different sizes (Razafimbelo et al, 2013). The collaboration of organic matter in soil for building aggregates in several land use managements had, variety of influences on the fate of PAHs, reported by Xiao et al (2014).…”
Section: Phytoremediation Of Hc and Soil Structurementioning
confidence: 99%
“…In an experiment referring to the interaction between soil aggregation and hydrocarbon contamination Amellal et al (2001) indicated that, more PAHs were found in the smaller size fractions (clay < 2 µm and fine silt 2 to 20 µm) compared to the sand and coarse silt. This accumulation and binding process is driven predominantly by the organic carbon content of the fractions (Tan et al, 2007;Guimara et al, 2013;Razafimbelo et al, 2013). The degrading microbes of PAHs were also distributed un-evenly through out the soil particles with different sizes (Razafimbelo et al, 2013).…”
Section: Phytoremediation Of Hc and Soil Structurementioning
confidence: 99%
See 2 more Smart Citations